2015
DOI: 10.1186/s12864-015-1213-1
|View full text |Cite
|
Sign up to set email alerts
|

Cetaceans evolution: insights from the genome sequences of common minke whales

Abstract: BackgroundWhales have captivated the human imagination for millennia. These incredible cetaceans are the only mammals that have adapted to life in the open oceans and have been a source of human food, fuel and tools around the globe. The transition from land to water has led to various aquatic specializations related to hairless skin and ability to regulate their body temperature in cold water.ResultsWe present four common minke whale (Balaenoptera acutorostrata) genomes with depth of ×13 ~ ×17 coverage and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Our data showed that ATZ treatment does not affect the relative proportion of cell types in the testes (Supplementary Figure S3A–E). Furthermore, we did not observe any significant changes in body or organ weights (Supplementary Figure S4A and B) or any decrease in testosterone and Follicle-stimulating hormone (FSH) levels (Supplementary Figure S4C), which are the expected outcomes of ATZ treatment in adult males (42). We cannot exclude the possibility that a subtle phenotype exists in F3 ATZ-lineage males that is not detectable by these methods.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Our data showed that ATZ treatment does not affect the relative proportion of cell types in the testes (Supplementary Figure S3A–E). Furthermore, we did not observe any significant changes in body or organ weights (Supplementary Figure S4A and B) or any decrease in testosterone and Follicle-stimulating hormone (FSH) levels (Supplementary Figure S4C), which are the expected outcomes of ATZ treatment in adult males (42). We cannot exclude the possibility that a subtle phenotype exists in F3 ATZ-lineage males that is not detectable by these methods.…”
Section: Resultsmentioning
confidence: 82%
“…Nr5a2 is highly expressed during development and the knockdown of Nr5a2 in zygote leads to downregulation of Pou5f1 expression (24). In our previous work we showed that mice exposed to ATZ have a higher number of H3K4me3 peaks that contain Nr5a2 motif (42). It has also been shown before that ATZ activates NR5A receptors (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we have a good idea about the types of cells that form somatic embryos in vitro (Filonova, Bozhkov, & Arnold, 2000; Toonen et al., 1994) and the cellular characteristics of these cells (Emons, 1994; Verdeil et al., 2007; Yeung, 1995), the process remains largely undescribed at the molecular level. High throughput expression analyses have been used to identify characteristics of embryogenic explants (Salvo, Hirsch, Buell, Kaeppler, & Kaeppler, 2014; Trontin, Klimaszewska, Morel, Hargreaves, & Lelu‐Walter, 2016; Wickramasuriya & Dunwell, 2015; Yang et al., 2012), but most studies use whole explants, which contain a complex mixture of tissues and cell types, making it difficult to specifically assign molecular identities to embryogenic cells. In situ gene expression analyses would help to resolve the sometimes contradictory relationship between expression of developmental marker genes and cell fate in different culture systems (Miguel & Marum, 2011) and provide a more exact description of when and how embryogenic cells are formed in culture (Li et al., 2014; Soriano et al., 2014).…”
Section: Definitions and Conceptsmentioning
confidence: 99%